Serbia Systematic Country Diagnostic : Update - World Bank (World Bank, Washington, DC, 2020)
The Systematic Country Diagnostic (SCD) examines the key constraints and opportunities to sustainably accelerate poverty reduction and boost shared prosperity. This SCD Update provides an update to the first comprehensive SCD published in 2015, titled “Serbia’s Potential for Sustainable Growth and Shared Prosperity.” The SCD Update reflects new important economic developments, includes an updated analysis of key constraints (informed by new data and recent developments), and updates the country’s priorities. It focuses on the goals of sustained poverty reduction and shared prosperity and builds on available data and recent evidence, including the World Bank’s Country Economic Memorandum “Serbia’s New Growth Agenda: Forging a New Future” (2019) and other analytical reports.